Pendapatan Premi, Risk Based Capital dan Laba Perusahaan : Studi pada Perusahaan Asuransi yang Terdaftar pada Bursa Efek Indonesia - Hidayat, Syarif (Insan Cita Bongaya Research Journal, 2025)
This study aims to test and analyze the influence of premium income and risk based capital. The research was conducted on insurance companies listed on the Indonesia Stock Exchange in 2020-2022 using the purposive sampling method, so that the sample number for this study is 45 financial statement data of insurance companies listed on the IDX for 3 years. The analysis method used in this study is linear regression analysis. The results of the study show that premium income has no effect on the company's profit. Risk-based capital has a significant positive effect on the company's profit